Understanding Flight Attendant Motivation Through Maslow's Hierarchy Theory - I Wayan Sunarsa; I Wayan Seniartha; Ni Ketut Sekarti; Ni Ketut Iswarini; Putu Gede Eka Darmaputra (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to understand the work motivation of flight attendants at Hotel X through the application of Maslow's Hierarchy of Needs Theory. Maslow's theory offers an effective framework for identifying and analyzing the various levels of needs that influence employee motivation, particularly in the context of housekeeping work. The methodology used was a qualitative approach with in-depth interviews with flight attendant employees. The results showed that the flight attendants' basic needs, such as salary and security, were generally met, although there were aspects that needed improvement, such as the maintenance of work equipment. Good social relationships and recognition of employee contributions significantly increased their sense of self-worth and motivation. Employees also showed high career aspirations and a desire for further development. Recommendations for Hotel X include improving the efficiency of work equipment replacement, strengthening safety and health, conducting team-building activities, implementing a reward program, providing career training, and regularly evaluating programs to improve employee motivation and well-being.